2015
DOI: 10.18270/rt.v12i2.758
|View full text |Cite
|
Sign up to set email alerts
|

Electro-myographic patterns of sub-vocal Speech: Records and classification

Abstract: Abstracthis paper describes the results obtained from recording, processing and classification of words in spoken Spanish by means of analysis of subvocal speech signals. The processed database has six words (forward, backward, right, left, start and stop), In this article, the signals are sensed with surface electrodes (placed on the surface of the throat) and acquired at a sampling frequency of 50 kHz. The signal conditioning consists of a couple of steps, namely the location of area of interest, using energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 3 publications
0
9
0
2
Order By: Relevance
“…Wand et al [5] achieved a 34.7% word error rate (WER) on 50 phrases using sEMG signals of 6 facial muscles from 6 subjects. Mendoza et al [6] obtained a WER of 25% from a single sEMG channel but only for 6 Spanish words. Wand et al reported a 54.7% WER on 50 phrases using 35 sEMG channels and 6 subjects [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wand et al [5] achieved a 34.7% word error rate (WER) on 50 phrases using sEMG signals of 6 facial muscles from 6 subjects. Mendoza et al [6] obtained a WER of 25% from a single sEMG channel but only for 6 Spanish words. Wand et al reported a 54.7% WER on 50 phrases using 35 sEMG channels and 6 subjects [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reason can be attributed to the nature of the sEMG signal, which is highly variant from subject to subject depending on the muscle strength and gender. Most of the reported research uses facial muscles to capture speech signals [6]- [8]. While giving better accuracy, this placement isn't user friendly and may not lend itself to practical implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar devices have been made as shown in projects such as [23] and [33] in which said projects employ wavelet analysis (explained in much greater detail later in chapter 3) in order to effectively process subvocal speech to allow said subvocal speech to be more easily classified as its intended speech for the final output. The wavelet analysis allows these devices to classify subvocal speech up to accuracies between 70% and 80%, but only through the use of expensive and not pocket-sized equipment.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…As previously mentioned, the motivation before this project was inspired papers such as "Electro-myographic patterns of sub-vocal Speech: Records and classification," by L. E. Mendoza, J. P. Rodríguez, and J. L. R. Valencia [23] and "Sub-vocal Phoneme-Based EMG Pattern Recognition and its application in Diagnosis," by M. Jahan and M.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation